The Role of Social Support and Academic Infrastructure on Student Learning Achievement with Learning Intensity - Hidayatullah, M. Iqbal; Surianto, Moh. Agung; Desembrianita, Eva (MANAZHIM, 2024)
This research is based on the research gap between the involvement of social support and academic infrastructure on student learning achievement. High or low social support has no effect on learning achievement, but if it is mediated by learning intensity, there is an influence on learning achievement. The aim of the research is to examine the influence of Social Support and Academic Infrastructure on Academic Achievement with mediation in the form of Learning Intensity for Muhammadiyah University Gresik students. The location of the research was at Muhammadiyah University Gresik which has a population of 5,411 people. This research uses quantitative methods with a population of all Muhammadiyah University Gresik students, using Stratified Random Sampling for each faculty. The number of samples obtained was 372 respondents. The results of this research show that (1) Social Support does not have a significant influence on Learning Achievement, (2) Academic Infrastructure has a significant influence on Learning Achievement, (3) Learning Intensity has a significant influence on Learning Achievement, (4) Social Support also influences Learning Intensity, ( 5) Academic Infrastructure has a significant effect on Learning Achievement, (6) For the results of the indirect effect test through the mediating variable Learning Intensity, Social Support has a significant effect on Learning Achievement with the mediation of Learning Intensity, (7) Academic Infrastructure has a significant effect on Learning Achievement with the mediation of Intensity.